Gestación subrogada en México: su proyección en las relaciones privadas internacionales / Surrogacy in Mexico: its projection in international private relations - Karla Cantoral Domínguez (Barataria, 2019)
In Mexico since 1997 surrogacy has been practiced as an assisted reproductive technology; however the lack of appropriate legislation has generated various problems in the national and international context. The objective of this article is to analyze the evolution of surrogacy cases in southeastern Mexico from 1997 to 2019 to assess their legal implications in international private relations, taking into consideration the best interests of the minor, the right of family, reproductive rights and international public order. It is proposed that gestational surrogate be protected by the law, taking into account the new paradigms in family law and reproductive rights, which guarantee in international private relations the protection of the best interests of the child as well as equality and non-discrimination in regarding the nationality of the parents.